Abituzumab combined with cetuximab plus irinotecan versus cetuximab plus irinotecan alone for patients with KRAS wild-type metastatic colorectal cancer: the randomised phase I/II POSEIDON trial. (15th October 2014) - Élez, E.; Kocáková, I.; Höhler, T.; Martens, U. M.; Bokemeyer, C.; Van Cutsem, E.; Melichar, B.; Smakal, M.; Csőszi, T.; Topuzov, E.; Orlova, R.; Tjulandin, S.; et al.
Abstract : The humanised αν integrin-inhibitory monoclonal antibody abituzumab may extend overall survival when combined with cetuximab and irinotecan in patients with KRAS wild-type metastatic colorectal cancer with high integrin αvβ6 expression. The tolerability of abituzumab in combination with cetuximab and irinotecan is acceptable. Abstract : Background: Integrins are involved in tumour progression and metastasis, and differentially expressed on colorectal cancer (CRC) cells. Abituzumab (EMD 525797), a humanised monoclonal antibody targeting integrin αν heterodimers, has demonstrated preclinical activity. This trial was designed to assess the tolerability of different doses of abituzumab in combination with cetuximab and irinotecan (phase I) and explore the efficacy and tolerability of the combination versus that of cetuximab and irinotecan in patients with metastatic CRC (mCRC) (phase II part). Methods: Eligible patients had KRAS (exon 2) wild-type mCRC and had received prior oxaliplatin-containing therapy. The trial comprised an initial safety run-in using abituzumab doses up to 1000 mg combined with a standard of care (SoC: cetuximab plus irinotecan) and a phase II part in which patients were randomised 1 : 1 : 1 to receive abituzumab 500 mg (arm A) or 1000 mg (arm B) every 2 weeks combined with SoC, or SoC alone (arm C). The primary end point was investigator-assessed progression-free survival (PFS). Secondary end points included overall survival (OS), response rate (RR) and tolerability. Associations between tumour integrin expression and outcomes were also assessed. Results: Phase I showed that abituzumab doses up to 1000 mg were well tolerated in combination with SoC. Seventy-three (arm A), 71 (arm B) and 72 (arm C) patients were randomised to the phase II part. Baseline characteristics were balanced. PFS was similar in the three arms: arm A versus SoC, hazard ratio (HR) 1.13 [95% confidence interval (CI) 0.78–1.64]; arm B versus SoC, HR 1.11 (95% CI 0.77–1.61). RRs were also similar. A trend toward improved OS was observed: arm A versus SoC, HR 0.83 (95% CI 0.54–1.28); arm B versus SoC, HR 0.80 (95% CI 0.52–1.25). Grade ≥3 treatment-emergent adverse events were observed in 72%, 78% and 67% of patients. High tumour integrin αvβ6 expression was associated with longer OS in arms A [HR 0.55 (0.30–1.00)] and B [HR 0.41 (0.21–0.81)] than in arm C. Conclusion: The primary PFS end point was not met, although predefined exploratory biomarker analyses identified subgroups of patients in whom abituzumab may have benefit. The tolerability of abituzumab combined with cetuximab and irinotecan was acceptable. Further study is warranted. ClinicalTrials.gov identifier: NCT01008475